The Lost Heritage of the South China Sea Trade, Fishing, and Religion as Expressions of Popular Sovereignty - Hoskin, Mark (Asia in World Politics: Past, Present, and Future, 2021)
China has a long history of fishing, trading, and settlement across the South China Sea. Recently, this maritime and economic history has been widely debated in Western countries as China reminds the world of her maritime heritage. Due to this disconnect, use of Western primary sources may be the key to unlocking the path for a common understanding of this history.